A descriptive analysis of computerized accounting information system: the case of SME in Somalia - Salad Abdulle, AbdiSalam; Zainol, Zaini; Ahmad @ Abdul Mutalib, Hawa (Readers Insight Publisher, 2019)
This study attempts to understand the usage of computerized accounting information system (CAIS) and its impact on the performance of SMEs in Somalia. Survey questionnaire is designed and distributed to selected SMEs in the capital city of Mogadishu, Somalia. The results of CAIS’s impact are discussed from four components of balanced scorecard and internal control perspectives. The results of this study may provide knowledge about the impact of usage CAIS for SMEs performance in Somalia and also provide some suggestions to the Somalian government on assistance needed for accounting reporting to improve further SMEs in Somalia. Based on finding, internal business process recorded the highest score i.e mean of 4.13 out of 5.00. It is implied that SMEs responded with challenging ICT business environment with adopting CAIS to improve its bottom line which is business processes.